MATH OBJECT IDENTIFICATION ON MATERIAL CULTURE ON THE ISLAND OF AMBON - Ratumanan, Tanwey Gerson; Laurens, Thereisa; Mataheru, Wilmintjie (Program Studi Pendidikan Matematika FKIP Universitas Pattimura, 2023)
Mathematics learning will be more interesting if aspects of the cultural context around students are involved. In this regard, the identification of cultural aspects of both material and non-material culture needs to be continuously carried out and integrated into learning. This research is an exploratory study to identify the material culture in villages in the Central Maluku district on Ambon Island. There are 3 (three) sub-districts in the administrative area of Central Maluku Regency located on Ambon Island. In each sub-district, one village was selected as a sample village, considering that (1) the village is a traditional village and (2) cultural objects are still well preserved. In the Leihitu sub-district, Negeri/Village Hila was selected; in the West Leihitu sub-district, Negeri/Village Allang was selected; and in the Salahutu sub-district, Negeri/Village Tulehu was selected. Data collection was done through observation and interviews. Data were analyzed using descriptive qualitative. The identification process found that the material culture, in the form of traditional houses, bailey, forts, old churches, old mosques, fishing facilities, weaving, and food, is related to mathematical objects. Material culture can be a cultural context that is integrated into learning the concept of flat and spatial shapes